Shared and distinct mechanisms of fibrosis - Distler, Jörg; Györfi, Andrea-Hermina; Ramanujam, Meera; Whitfield, Michael L.; Königshoff, Melanie; Lafyatis, Robert (Nature Reviews Rheumatology, 2019)
Fibrosis is defined as an excessive deposition of connective tissue components and can affect virtually every organ system, including the skin, lungs, liver and kidney. Fibrotic tissue remodelling often leads to organ malfunction and is commonly associated with high morbidity and mortality. The medical need for effective antifibrotic therapies is thus very high. However, the extraordinarily high costs of drug development and the rare incidence of many fibrotic disorders hinder the development of targeted therapies for individual fibrotic diseases. A potential strategy to overcome this challenge is to target common mechanisms and core pathways that are of central pathophysiological relevance across different fibrotic diseases. The factors influencing susceptibility to and initiation of these diseases are often distinct, with disease-specific and organ-specific risk factors, triggers and sites of first injury. Fibrotic remodelling programmes with shared fibrotic signalling responses such as transforming growth factor-β (TGFβ), platelet-derived growth factor (PDGF), WNT and hedgehog signalling drive disease progression in later stages of fibrotic diseases. The convergence towards shared responses has consequences for drug development as it might enable the development of general antifibrotic compounds that are effective across different disease entities and organs. Technological advances, including new models, single-cell technologies and gene editing, could provide new insights into the pathogenesis of fibrotic diseases and the development of drugs for their treatment.
CRIS-Team Scopus Importer:2019-11-29